Globalisasi ekonomi dan impaknya kepada ruang budaya bandar Malaysia - Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
This paper attempts to make the point that economic globalization has impacted Malaysian urban cultural space although it is not a process that goes unchallenged. By alluding to the progressive formation of a new cultural area in Bangsar, Kuala Lumpur the impact is illustrated through newspaper accounts of the attempt by relevant parties to Westernise or Americanise both the landscape and cultural activities of Bangsar. In terms of landscape, the relatively strong presence of expatriates has led to the setting up of bistros, pubs and massage parlours along the Bangsar Baru streets. In terms of cultural activities, agents had sought to introduce bold new attractions such as the bubble bath after the fashion of the Woodstock Musical and Fair festival during a Valentine Day celebration in 2000 which ended up attracting solid resistence from the nearby mosque community and forced the state to have it cancelled. While this significantly shows the ability of the local to influence the impact of the global, it should not be interpreted as an act of acquiescence on the part of the state with regard to the local counteraction. In wanting to safeguard Malaysia’s competitiveness, the state’s interest is still uppermost in getting the local public tolerating, if not accepting, the ‘global’ culture. It is only political pragmatism that forced it to side with the local resistence. In other words, it is the split personality of the state that has facilitated the encroachment and penetration of the Malaysian cultural space by the global sensate culture